2020
DOI: 10.1080/09546634.2020.1808154
|View full text |Cite
|
Sign up to set email alerts
|

Examining recommendations for the use of biologics and other systemic therapies during COVID-19: a review and comparison of available dermatology guidelines and patient registries

Abstract: Background: The novel coronavirus has an affinity for almost every organ system, including the skin. This review article will compile and compare dermatology guidelines related to the dermatologic care of patients during the COVID-19 pandemic. Objective: To review and compare the available guidelines and recommendations on use of biologics and other systemic therapies in dermatology patients. Methods: We conducted a search for guidelines and recommendations for dermatology providers, with specific attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…People with psoriasis undergoing systemic therapy should be advised to follow current guidelines for hygiene and physical distancing as recommended in their respective area of residence. Given that this is a novel and rapidly changing situation, recommendations may be modified as more data become available [52].…”
Section: Discussionmentioning
confidence: 99%
“…People with psoriasis undergoing systemic therapy should be advised to follow current guidelines for hygiene and physical distancing as recommended in their respective area of residence. Given that this is a novel and rapidly changing situation, recommendations may be modified as more data become available [52].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based cohort study of psoriasis patients in Israel indicated that IL-17A inhibitor treatment was not associated with an increased risk of developing COVID-19 infection, hospitalization or mortality compared with methotrexate or with non-systemic/non-immunomodulatory agents [ 80 ]. Current recommendations advise continuing biological therapy in patients who do not have severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection, and temporarily discontinuing treatment in those who test positive for the infection [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anecdotal data suggest that some patients with psoriasis discontinued treatment with their biological therapy because they feared that it would increase their risk of developing COVID-19 infection [ 82 ]. This highlights the need for individualized treatment decisions and good communication between patients and physicians about the risks and benefits of treatment versus no treatment during the COVID-19 pandemic [ 81 , 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…For those patients who are qualified for biological treatment but have not yet started, it is advisable to carefully assess the balance of benefits and risks of treatment for each patient. In populations with a high risk for severe COVID-19, a postponement of biological treatment or other therapeutic options should be considered (79)(80)(81). The National Psoriasis Foundation COVID-19 Task Force has reiterated a similar point in the guidance for the management of psoriatic disease during the pandemic.…”
Section: Recommendations For the Use Of Biologics During The Pandemic Of Covid-19mentioning
confidence: 99%